2012
DOI: 10.1128/jb.00553-12
|View full text |Cite
|
Sign up to set email alerts
|

Defective Lipoprotein Sorting Induces lolA Expression through the Rcs Stress Response Phosphorelay System

Abstract: cThe Escherichia coli LolA protein is a lipoprotein-specific chaperone that carries lipoproteins from the inner to the outer membrane. A dominant negative LolA mutant, LolA(I93C/F140C), in which both 93 Ile and 140 Phe are replaced by Cys, binds tightly to the lipoprotein-dedicated ABC transporter LolCDE complex on the inner membrane and therefore inhibits the detachment of outer membrane-specific lipoproteins from the inner membrane. We found that the expression of this mutant strongly induced lolA gene tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 44 publications
1
36
0
Order By: Relevance
“…Mislocalization of lipoproteins has been shown to cause induction of the Rcs pathway (53). Consistent with the positive regulation of the rpoEP3 promoter by the Rcs system, its activation by overexpression of the lipoproteins is also Rcsdependent.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Mislocalization of lipoproteins has been shown to cause induction of the Rcs pathway (53). Consistent with the positive regulation of the rpoEP3 promoter by the Rcs system, its activation by overexpression of the lipoproteins is also Rcsdependent.…”
Section: Discussionmentioning
confidence: 52%
“…We reasoned that the increased synthesis of lipoprotein could cause limitation of the Lol system required for sorting of lipoproteins. Defective lipoprotein is known to induce the Rcs pathway (53). Thus, we tested if the mechanism of activation of the rpoEP3 promoter was also Rcs-dependent.…”
Section: The Overexpression Of Genes Encoding Lipoproteins Induces Thmentioning
confidence: 99%
“…While the mechanistic basis of RcsF signal transduction to the sensor kinase RcsC has not yet been determined, it has been shown that both perturbations to the outer-membrane and sensing of mislocalization of outer-membrane lipoproteins stimulate RcsF signaling to RcsC [38,39]. Thus, activation of the LEE in TW14359DtolA may be due to RcsF sensing of pleiotropic cellular effects following loss of TolA.…”
Section: Discussionmentioning
confidence: 96%
“…Signal transduction to RcsC and Rcs phosphorelay activation typically requires the action of an additional factor, RcsF, which is a~14-kDa outer-membrane bound lipoprotein that orients towards the periplasm [37]. RcsF signaling has been demonstrated for mutations that affect the proper folding of periplasmic proteins, as well as those which disrupt the proper synthesis and localization of lipopolysaccharides and lipoproteins [38,39]. Activity is dependent on both the formation of nonconsecutive disulfides and an unstructured proline rich region to properly convey signals to the sensor kinase RcsC for Rcs phosphorelay activation [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis demonstrated that increased transcription of lipoprotein transporters and lipoproteins in LOSdeficient A. baumannii resulted in outer-membrane remodeling that could promote A. baumannii survival without lipid A/LOS. Regulation of lolA in E. coli is controlled by the Rcs phosphorelay system, which detects cell-envelope stress (33). However, A. baumannii does not encode an orthologous system, and regulatory mechanisms controlling lolA gene expression in A. baumannii are not known.…”
Section: Discussionmentioning
confidence: 99%